2009
DOI: 10.1016/j.bbrc.2009.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Lipid nanopores can form a stable, ion channel-like conduction pathway in cell membrane

Abstract: Cell permeabilization by electric pulses (EPs), or electroporation, has been well established as a tool to indiscriminately increase membrane flows of water solutes down the concentration and voltage gradients. However, we found that EPs of nanosecond duration (nsEPs) trigger formation of voltagesensitive and inward-rectifying membrane pores. NsEP-treated cells remain mostly impermeable to propidium, suggesting that the maximum pore size is ~1 nm. The ion-channel-like properties of nsEP-opened nanopores vanish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
221
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(244 citation statements)
references
References 23 publications
(21 reference statements)
23
221
0
Order By: Relevance
“…Previous work by our group and others has shown that nsPEFs can cause ion influx into a cell and that these same pulses disrupt the symmetry of the plasma membrane. 7,10,11 We have observed that Ca 2þ ions flood into the cytoplasm and remain elevated beyond 20 s post exposure. Experiments performed in the absence of extracellular Ca 2þ showed no changes in intracellular Ca 2þ , suggesting that the release of Ca 2þ from intercellular stores is likely not responsible for the observed Ca 2þ burst.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous work by our group and others has shown that nsPEFs can cause ion influx into a cell and that these same pulses disrupt the symmetry of the plasma membrane. 7,10,11 We have observed that Ca 2þ ions flood into the cytoplasm and remain elevated beyond 20 s post exposure. Experiments performed in the absence of extracellular Ca 2þ showed no changes in intracellular Ca 2þ , suggesting that the release of Ca 2þ from intercellular stores is likely not responsible for the observed Ca 2þ burst.…”
Section: Discussionmentioning
confidence: 97%
“…Nanopore formation, in contrast to the larger pores formed by longer pulses (electroporation), are less likely to pass large ions such as propidium, but freely allow passage of small ions. 7,8 Various studies using diverse techniques such as electrophysiology, [9][10][11] fluorescence microscopy, 7,11 and direct ion measurement in bulk solution for longer pulse widths 12 have supported the hypothesis that such "nanopores" exist. Interestingly, when exposed cells are under a whole cell patch clamp, nanopore activity appears to have unique electrical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…10−12 In contrast to conventional electroporation, under certain conditions, nsPEFs create small, propidium iodide (PI)-impermeable pores in plasma membranes and intracellular organelles, called nanopores. 13,14 The formation of high-density nanopores in all cell membranes is referred to as supraelectroporation. 15,16 These plasma membrane nanopores are long lasting (minutes) and exhibit complex ion channel-like conductance that is voltage-sensitive and inwardly rectifying.…”
mentioning
confidence: 99%
“…These nanopores are hypothesized to induce many nsPEF effects. 14,16,17 NsPEF effects occur in the absence of ligands or receptors. NsPEFs have been shown to breach intracellular granules, 9 to mobilize Ca 2+ from the ER and through plasma membranes, 18−20 and to modulate intracellular Ca 2+ levels in chromaffin cells, mostly or exclusively through nanopores in the plasma membranes.…”
mentioning
confidence: 99%
“…Among various modifiers, N-trimethyl chitosan chloride (TMC) has been widely used as an absorption enhancing agent in the new delivery systems of peptides, proteins and other macromolecules (Pakhomov et al, 2010;Katrin & Shlomo, 2012). TMC is a partially quaternized derivative of chitosan, characterized by superior water solubility and permeation enhancing effect in neutral environment (Amidi et al, 2006;Florea et al, 2006).…”
Section: Introductionmentioning
confidence: 99%